Specification for harmonized system of quality assessment for electronic components. Fixed capacitors for use in electronic equipment. Blank detail specification: fixed metallized polycarbonate film dielectric d.c. capacitors. Assessment level E. (31st May 1990) - British Standards Institution,
No abstract available